2018
DOI: 10.1111/ijcp.13263
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for infection in patients with chronic leg ulcers: A survival analysis

Abstract: Aim:This study aimed to validate the relationships between possible predictive factors and clinically diagnosed infection in adult patients with chronic leg ulcers. Methods:This study used a sample of 636 adult participants whose ulcers were diagnosed as either venous, arterial or mixed aetiology leg ulcers and had no clinical signs of infection at recruitment. Data were extracted from recruitment to 12 weeks from six longitudinal prospective studies from 2004 to 2015. Survival analysis was used to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 38 publications
5
17
0
3
Order By: Relevance
“…The current study found no associations between other medical conditions and infection, including peripheral vascular disease, diabetes mellitus, rheumatoid arthritis and unhealthy weight, which is similar to those from Bui, Finlayson, et al (). Corticosteroids were reported to increase skin and soft tissue infection (Germano et al, ) and acute wound infection (Finan et al, ).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The current study found no associations between other medical conditions and infection, including peripheral vascular disease, diabetes mellitus, rheumatoid arthritis and unhealthy weight, which is similar to those from Bui, Finlayson, et al (). Corticosteroids were reported to increase skin and soft tissue infection (Germano et al, ) and acute wound infection (Finan et al, ).…”
Section: Discussionsupporting
confidence: 90%
“…The ability to recognise people at risk of developing infection early lies in the understanding of associations between potential risk factors and infection. The current research, a prospective study, confirmed the finding from a previous study relied on a secondary analysis by Bui, Finlayson, et al () that the use of walking aids can be a risk factor for developing infection in patients with CLUs. Walking aids applied to all devices that were used by patients to assist their mobility.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations